STUDY OF THE RELATIONSHIP BETWEEN WORKPLACE DESIGNING AND INDIVIDUAL EFFICIENCY AMONG THE PERSONNEL OF TEHRAN SHAHID MODARRES HOSPITAL IN 2015 - SHAIRI, ELHAM; VAHDAT, SHAGHAYEGH; ASL, IRAVAN MASOUDI (International Journal of Clinical and Biomedical Research, 2016)
Introduction: Today, one of main priorities of managers is increasing efficiency and improvement of provided services in health and treatment domain for increasing people satisfaction. By increasing efficiency in their organizations, managers could pave the way for achieving organizational aims and the country development in health and treatment domain. Regarding the different designing of workplace and factors effective on personnel efficiency in various organizations, this study has been performed with the aim of examining the relation between workplace designing and personnel efficiency. Materials and Methods: The present descriptive study was performed in 2015 in cross-sectional form. The study statistical population was constituted from 750 persons of Tehran Shahid Modarres hospital personnel. For collecting data, scholar- made questionnaire was used whose validity was confirmed. In this study, 107 men and 175 women randomly completed the questionnaire that totally 282 people were examined. The questionnaire validity was calculated using Cronbach alpha between 0.691 and 0.701. Data obtained from the questionnaire was analyzed using SPSS software and statistical analysis (variance analysis, dependent T-test, Pierson correlation test, regression). In data analysis the highest and lowest score was 1 and 5. Results: Findings indicate that workplace physical factor including furniture, temperature, noise and music had significant relations with efficiency and lighting and spatial arrangement did not have any significant relation with efficiency. Generally, temperature with correlation (0.241) had the highest impact and noise (0.137) had the least impact on efficiency. Conclusion: Improvement and suitable designing of workplace leads satisfaction and increasing personnel efficiency.